Analysis Transformation and Digitalization of MSMes ( Literature Review) - Rahman Soesilo; Liosten Rianna Roosida Ully Tampubolon (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of the research is to describe and provide a written explanation of the variables using a literature review of various scientific articles related to the scientific article. The research results of digitization transformation with significant productivity, transformation with significant added value,transformation with significant downstream research use qualitative methods. Suggestions for the future with the current limitations of researchers in searching for literature reviews, the results of this study can add characteristics and knowledge in digitalization transformation in general. The novelty of this study is that there is a significant relationship between variables and can be made in the latest framework.